Diprosopus y otras malformaciones en bovino: Reporte de Caso - Gaona Huamán, Edson (2025)
Diprosopus is a congenital malformation result, also known as craniofacial duplication, which is widely recognized in humans and there are also reports in many animal species. The objective of this research is to learn about the clinical manifestations and post mortem findings in cattle diprosopus. Female cattle with incomplete cephalic facial cephalic duplication (diprosopus), product of the eighth gestation of a Creole cow with, from the village center of Quidén, district of Paccha, province of Chota, region of Cajamarca, Peru, with extensive production breeding system. The cattle presented two lower jaws with double oral and nasal cavity, two tongues and supernumerary teeth, the vault was double and single neck. It is confirmed that the case described is diprosopus in cattle.